2015
DOI: 10.4236/jhrss.2015.32010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Perceived Insider Status

Abstract: Perceived Insider Status (PIS) is defined as the extent to which an individual employee perceives him or herself as an insider within a particular organization. It represents that employees have earned a "personal space" and acceptance inside their work organization. Researches show that PIS has a strong effect on employee's job performance and organizational citizenship behavior (OCB), etc. Through a review of PIS, this paper places emphasis on the elaboration of influencing factors and mechanisms of PIS from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…For instance, [36] found that when employees perceive themselves as insiders of their organizations, they also accept citizenship responsibilities, which drive them to demonstrate more OCB. Furthermore, according to social exchange theory, when employees build a positive relationship with their organizations, they tend to engage in behaviors that go beyond the formal requirements of their jobs [51]. Hence, this study expects a positive relationship between perceived insider status and voluntary green behavior.…”
Section: The Mediating Role Of Perceived Insider Statusmentioning
confidence: 93%
“…For instance, [36] found that when employees perceive themselves as insiders of their organizations, they also accept citizenship responsibilities, which drive them to demonstrate more OCB. Furthermore, according to social exchange theory, when employees build a positive relationship with their organizations, they tend to engage in behaviors that go beyond the formal requirements of their jobs [51]. Hence, this study expects a positive relationship between perceived insider status and voluntary green behavior.…”
Section: The Mediating Role Of Perceived Insider Statusmentioning
confidence: 93%
“…In a similar vein, benefits provided by the organizations, as an employer, contribute to the formation of insider status of employees. According to Dai and Chen (2015) inducements provided by the organizations can be classified as economic inducements, inducements of development through training and advancement opportunities and social-emotional support through strong interaction with supervisors and colleagues. These rewards and inducements, based on the social exchange theory (Blau,1964), shape the perception of employees through showing the importance given to employees by the organization and prompt employees to the obligation of working better.…”
Section: Employer Brand and Perceived Insider Statusmentioning
confidence: 99%
“…In the past, researchers were defining PIS from two viewpoints: an employee’s self-concept and an employee-organization relationship (Dai and Chen, 2015). By using two different perspectives to define PIS, scholars have generally relied on various theories to explain their empirical results.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Perceived insider status represents the extent to which an employee perceives oneself as an insider within a particular organization ( Stamper and Masterson, 2002 ). In the past, researchers were defining PIS from two viewpoints: an employee’s self-concept and an employee-organization relationship ( Dai and Chen, 2015 ). By using two different perspectives to define PIS, scholars have generally relied on various theories to explain their empirical results.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation